2003
DOI: 10.1007/s00455-003-0022-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cuff Deflation and One-Way Tracheostomy Speaking Valve Placement on Swallow Physiology

Abstract: This study examined the effects of tracheostomy cuff deflation and one-way speaking valve placement on swallow physiology. Fourteen nonventilator-dependent patients completed videofluoroscopic swallow studies (VFSS) under three conditions: (1) cuff inflated, (2) cuff deflated, and (3) one-way valve in place. Four additional patients with cuffless tracheostomy tubes completed VFSS with and without the one-way valve in place. All swallows were analyzed for the severity of penetration/aspiration using an 8-point … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
121
1
11

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(136 citation statements)
references
References 29 publications
3
121
1
11
Order By: Relevance
“…16,17 It has been demonstrated that the inflated cuff anchors the trachea to the anterior part of the neck and results in reduced movement of the larynx and obstruction of the esophagus. [17][18][19][20] Suiter et al 21 demonstrated that deflation of the cuff reduced risk of aspiration of liquids and improved laryngeal excursion. Amathieu and colleagues 17 demonstrated that the swallowing reflex was progressively more difficult to elicit with increasing cuff pressure.…”
Section: Ten Steps Toward Decannulationmentioning
confidence: 99%
“…16,17 It has been demonstrated that the inflated cuff anchors the trachea to the anterior part of the neck and results in reduced movement of the larynx and obstruction of the esophagus. [17][18][19][20] Suiter et al 21 demonstrated that deflation of the cuff reduced risk of aspiration of liquids and improved laryngeal excursion. Amathieu and colleagues 17 demonstrated that the swallowing reflex was progressively more difficult to elicit with increasing cuff pressure.…”
Section: Ten Steps Toward Decannulationmentioning
confidence: 99%
“…Here, we have two airways to consider. Simple, easily reversible problems have caused significant morbidity and mortality in tracheostomy patients, including the presence of obstructing (decannulation) caps or obturators attached to the tracheostomy tubes [61][62][63]. Speaking valves can be used incorrectly (with an inflated, cuffed tube) and these, along with small humidifying devices (e.g.…”
Section: Assessment Of Tracheostomy Patencymentioning
confidence: 99%
“…It is noteworthy that the Brazilian Consensus on Mechanical Ventilation suggests that this pressure analysis should be perfomed daily 24 . It is recommended that the cuff pressure against the walls of the trachea allows adequate capillary blood flow, not to exceed physiological values around 25 mmHg (30 cmH2O), however, in clinical practice it is common that cuff measures are in disagreement with the recommended values in the literature 6,23 . It is recommended to check the cuff pressure three times a day.…”
mentioning
confidence: 99%
“…Other studies claim that the type and size of the cannula and the status of the cuff interfere in the functioning of swallowing 2,21 , worsening performance in situations of cuff inflated and deflated respectively 20 . However, some studies do not show correlation between the presence of tracheostomy and dysphagia 22,23 .…”
mentioning
confidence: 99%